(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article explores the multifaceted influence of international financial organizations (IFOs)—such as the World Bank, International Monetary Fund (IMF), Asian Development Bank (ADB), and Islamic Development Bank (IDB)—on projects in Uzbekistan. The research provides a critical and analytical perspective, examining IFOs’ role in shaping economic reform, infrastructure development, public policy, and socio-economic outcomes. By employing qualitative content analysis, case studies, and a review of both primary and secondary sources, the article identifies the opportunities created, the challenges encountered, and the nuances of IFO engagement in Uzbekistan’s development trajectory. Evidence suggests that while IFOs have contributed substantially to Uzbekistan’s modernization and reform, their involvement also raises questions of national sovereignty, dependency, and the alignment of development with societal needs.